THE DEVELOPMENT OF A COMPUTER DRIVEN JIGSAW - Lubbe, A.J.; Raath, H. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: With a jigsaw, sharp inside corners can only be sawn out if the blade of the jigsaw is lifted out of the material and the corner is approached from two different sides. For the blade to be able to re-enter the material no material must be present at the entry point. The most important feature of an automated jigsaw is that it should be able to round off inside corners on a contour and automatically return to these corners to remove material left between the round off and the contour. With this development project an automated jigsaw machine was designed, built and tested. Emphasis fell on the development of software that enables one to draw contours that need to be sawn out, change these contours into cutter paths for the jigsaw and transform the cutter paths into digital format necessary to control the jigsaw machine via the parallel port of a personal computer. AFRIKAANSE OPSOMMING: